2014
DOI: 10.1097/jto.0000000000000125
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of BIM Deletion Polymorphism in Non–Small-Cell Lung Cancer with Epidermal Growth Factor Receptor Mutation

Abstract: Background:Germline alterations in the proapoptotic protein Bcl-2–like 11 (BIM) can have a crucial role in tumor response to treatment. To determine the clinical utility of detecting BIM deletion polymorphism in non–small-cell lung cancer positive for epidermal growth factor receptor (EGFR) mutation, we examined outcomes of patients with and without BIM alterations.Methods:We studied 70 patients with EGFR mutation-positive non–small-cell lung cancer who were treated with an EGFR tyrosine kinase inhibitor betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 26 publications
4
42
1
Order By: Relevance
“…Lee et al also found that 3 of 11 patients showing primary resistance to EGFR-TKIs possessed this polymorphism, whereas BIM deletion polymorphism was not predictive of PFS for EGFR-TKIs [24]. Several studies reported contrary results associated BIM deletion with PFS [50][51][52]. Therefore, although we also detected this polymorphism in 4 of 21 patients, the exact role of BIM polymorphism in the response to EGFR-TKIs requires further investigation.…”
Section: Nocontrasting
confidence: 53%
“…Lee et al also found that 3 of 11 patients showing primary resistance to EGFR-TKIs possessed this polymorphism, whereas BIM deletion polymorphism was not predictive of PFS for EGFR-TKIs [24]. Several studies reported contrary results associated BIM deletion with PFS [50][51][52]. Therefore, although we also detected this polymorphism in 4 of 21 patients, the exact role of BIM polymorphism in the response to EGFR-TKIs requires further investigation.…”
Section: Nocontrasting
confidence: 53%
“…BIM mRNA expression is also implicated as an early adaptive biomarker of resistance in EGFRm NSCLC patients [39]; a subset analysis by EGFR-mutation type was not provided for this study. Similarly, BIM deletion polymorphisms were associated with shorter PFS in EGFRm patients treated with an EGFR-TKI [47,48]. As BIM polymorphisms constitute a germ-line alteration, their pattern of distribution should not differ significantly between EGFRmutation subtypes [49], thereby falling short of a plausible hypothesis to explain the lower efficacy of EGFR-TKIs in L858R-mutated patients.…”
Section: • Other Molecular Markers Of Resistance (Brca1 and Bim)mentioning
confidence: 91%
“…In some retrospective studies, PFS was significantly shorter upon EGFR TKI treatment in EGFR-mutant lung cancer patients with. These data suggest that BIM gene polymorphism could be postulated as a biomarker of EGFR TKI resistance, but larger prospective studies are required to justify that [77][78][79]. Histone deacetylase (HDAC) inhibition can restore BIM function and sensitize the cancer cells to EGFR TKI in patients with EGFR-mutant NSCLC in whom resistance is associated with a common BIM polymorphism [80].…”
Section: Potential Development Issuesmentioning
confidence: 96%